1979
DOI: 10.1136/thx.34.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracic manifestations in non-Hodgkin's lymphoma.

Abstract: A total of 16 of 86 patients (19%/,) with non-Hodgkin's lymphoma were found to have intrathoracic disease in this retrospective study. Paratracheal, mediastinal, and hilar lymphadenopathy was the commonest manifestation followed by pulmonary lesions and pleural effusion. The lymphoma was at an advanced clinical stage in all the patients with intrathoracic disease. About one-third of the intrathoracic lesions first developed at the time of relapse after successful initial therapy. There was a better response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…In most of the cases, serous cavity involvement is part of a disseminated disease process, with predominance of other thoracic organ involvement. Among 86 NHL cases, Manoharan et al 38 found intrathoracic disease in 16 (19%). Paratracheal, mediastinal, and hilar lymphadenopathy were the commonest manifestations followed by pulmonary lesions and pleural effusions.…”
Section: Clinical Presentation and Imaging Findings In Lymphoma Patiementioning
confidence: 97%
“…In most of the cases, serous cavity involvement is part of a disseminated disease process, with predominance of other thoracic organ involvement. Among 86 NHL cases, Manoharan et al 38 found intrathoracic disease in 16 (19%). Paratracheal, mediastinal, and hilar lymphadenopathy were the commonest manifestations followed by pulmonary lesions and pleural effusions.…”
Section: Clinical Presentation and Imaging Findings In Lymphoma Patiementioning
confidence: 97%
“…3 Moreover, pericardial lesions readily cause cardiac tamponade manifested by hypotension. 4,5 Severe right cardiac failure developed first in our patient because the tumor mass occupied almost the entire space of the right atrial cavity and invaded its wall. Irradiation and chemotherapy are generally considered effective against malignant lymphoma; however, we decided to perform an emergency operation first due to the moribund condition of the patient.…”
Section: Discussionmentioning
confidence: 95%
“…5 The latter may consist of single or multiple nodules, pneumonic areas, or peribronchial infiltration 44-6 all cases being associated with extrathoracic manifestations of lymphoma in one study 4.…”
Section: Discussionmentioning
confidence: 99%
“…Previously it has been noted that there is an increased incidence of malignant lung tumours, particularly adenocarcinomas and bronchiolar-alveolar carcinomas, in fibrotic scars in the lung 23 Although intrathoracic involvement in non-Hodgkin’s lymphoma is common (occurring in about 10–25% of cases),4 5 it has not been described arising in an area of CFA.…”
Section: Discussionmentioning
confidence: 99%